2000
DOI: 10.1021/la990943d
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion Polymerization of Aniline in Different Media:  A UV−Visible Spectroscopic and Kinetic Study

Abstract: The course of dispersion polymerization of aniline using ammonium peroxodisulfate (APS) as initiator oxidant and poly(vinyl alcohol) as stabilizer in different media, viz., water (1 M HCl), water (pH ) 2.41, [aniline] ≡ [HCl]), and aqueous ethanol (1 M HCl), was followed spectrophotometrically. It was found that the absorption peak positions for the pernigraniline salt change markedly with change in acidity and [APS]/[aniline] ratio. The spectral shape also changes greatly when water is replaced by aqueous eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 54 publications
2
46
0
Order By: Relevance
“…also been reported by Chakraborty and Mandal (24,25). Gill et al (26) observed an increase in the oxidation rate after the introduction of nanocolloidal silica but no acceleration effect was found when poly(ethylene oxide)-based stabilizer was used.…”
Section: The Film Thickness D (Open Triangles) Is Compared With Thementioning
confidence: 58%
“…also been reported by Chakraborty and Mandal (24,25). Gill et al (26) observed an increase in the oxidation rate after the introduction of nanocolloidal silica but no acceleration effect was found when poly(ethylene oxide)-based stabilizer was used.…”
Section: The Film Thickness D (Open Triangles) Is Compared With Thementioning
confidence: 58%
“…Analysis of more than 20 sets of UV-Vis spectra showed the characteristic traces seen in Figure 2 [54] It is known that upon oxidation by APS, oligoanilines are rapidly protonated to form PNS, absorbing light at around 650-700 nm. [54]b As the reaction progresses, PNB (%550 nm) can be observed (at %40 min in our system) until the APS is consumed, as PNB react with aniline to form ES (47 min).…”
Section: Resultsmentioning
confidence: 98%
“…[49,50] As the oxidation state changes, the UV-Vis absorption peak strength and/or peak position changes. [51] Thus, UV-Vis spectroscopy is widely used for characterizing PANI and studying the reaction kinetics in both electrochemical [52][53][54][55] and chemical oxidative polymerization [56][57][58][59][60] systems. Since PANI solution have high extinction coefficients even at a very low concentration, dilute reaction mixtures are usually required for in situ UVVis studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the aforementioned approaches, preparation of the colloidal PANI dispersion with the polymeric stabilizers is a widely accepted one. Poly(N-vinyl pyrrolidone), 19,20 poly (methyl vinyl ether), 21,22 poly(vinyl alcohol) (PVA), 23,24 poly[(N-vinylpyrrolidone)-co-(vinylalcohol)], 19 and poly(ethylene oxide) (PEO) 25 have been most frequently used as polymeric stabilizers for the colloidal PANI dispersions. Table 1 Correspondence concerning this article should be addressed to P. Liu at pliu@izu.edu.cn.…”
Section: Introductionmentioning
confidence: 99%